ISOLASI DAN IDENTIFIKASI SENYAWA FLAVONOID DALAM DAUN BELUNTAS (Pluchea indica L.) - Koirewoa, Yohanes Adithya; Fatimawali, Fatimawali; Wiyono, Weny (PHARMACON, 2012)
Isolation and identification flavonoid compounds in beluntas leaf (Pluchea indica L.) have been conducted. Isolation was carried out by using 96% p.a ethanol solvent of maceration extraction for 7 days and partition using n-heksana solvent to obtain concentrated beluntas leaf extract. The extract was purified by thin layer chromatography using eluent n-butanol : asetic acid : water (BAA) (4:1:5). Isolate 3, result from thin layer chromatography contain flavonoid compound. Ultra Violet - Visible spectra showed that the flavonoid compound was flavonol, with characteristic wavelengths from 250 to 280 nm for band II and 350-385 nm for band I. Keywords: beluntas, flavonoid, Thin Layer Chromatography, UV-Vis Spectrophotometer